Preparation and application of a silver ferrite / indium tin sulfide composite Z-type photocatalyst

By loading silver ferrite on the surface of indium tin sulfide to form a Z-shaped heterojunction structure, the problem of low efficiency of traditional photocatalysts in degrading antibiotic wastewater is solved, and a more efficient photocatalytic degradation effect is achieved.

CN116899590BActive Publication Date: 2025-03-25FUZHOU UNIV

Patent Information

Application Number
CN202310884082.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-03-25
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

Traditional semiconductor photocatalysts such as TiO2 and ZnO have problems with wide band gaps and low quantum efficiency, making it difficult to efficiently degrade antibiotic pollution in water bodies.

Method used

By loading the nanoparticle silver ferrate on the surface of the indium sulfide layer-like surface, a Z-type heterojunction structure is formed, and the separation efficiency of photogenerated electrons-holes is improved, thereby preparing a composite Z-type photocatalyst.

Benefits of technology

This photocatalyst can effectively improve the carrier life, reduce the electron-hole recombination rate, and significantly improve the degradation efficiency of antibiotic wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116899590B_ABST
    Figure CN116899590B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of photocatalytic materials, and specifically provides a preparation and application of a silver ferrite / indium tin sulfide composite Z-type photocatalyst, wherein the composite catalyst is a nanoparticle silver ferrite loaded on a lamellar indium tin sulfide. The silver ferrite / indium tin sulfide composite Z-type photocatalyst is prepared by a hydrothermal method. Compared with silver ferrite and indium tin sulfide, the silver ferrite / indium tin sulfide composite Z-type photocatalyst has improved photocatalytic activity, has the advantages of simple preparation method, easy process control, good photocatalytic activity, etc., is a new type of photocatalytic activity and has been successfully applied to antibiotic degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, specifically the field of photocatalysis, and relates to the preparation and application of a silver ferrite / indium tin sulfide composite Z-type photocatalyst. Background Art

[0002] Antibiotic pollution in water bodies is one of the most important concerns in global public health, and it poses a huge threat to global biodiversity and human health and safety. Semiconductor photocatalysts can be used to degrade organic pollutants (such as antibiotics). It is of great significance to solve environmental pollution problems. However, traditional semiconductor photocatalysts (such as TiO2, ZnO, etc.) have disadvantages such as wide band gap and low quantum efficiency. Therefore, it is of great significance to develop efficient visible light photocatalysts and give full play to the role of solar energy. Indium tin sulfide is a common ternary chalcogenide compound with a band gap of about 2.1eV and is a visible light responsive semiconductor. It is widely used in hydrogen production, CO2 reduction, organic matter degradation, etc. However, for single-component ternary metal sulfide semiconductors, it may have disadvantages such as photocorrosion and short carrier lifetime. Therefore, many heterostructure photocatalysts based on SnIn4S8, such as SnIn4S8 / MoS2, SnIn4S8 / SnO2, SnIn4S8 / TiO2 and SnIn4S8 / CeO2, etc. It was developed to enhance the separation of photoinduced charge carriers and thus improve the photocatalytic activity. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method and application of a silver ferrite / indium tin sulfide composite Z-type photocatalyst, wherein the obtained silver ferrite / indium tin sulfide composite Z-type photocatalyst is prepared by loading nanoparticles of silver ferrite on the surface of lamellar indium tin sulfide to form a Z-type heterojunction structure, thereby improving the separation efficiency of photogenerated electrons and holes to achieve effective degradation of antibiotic wastewater.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0005] A first aspect of the present invention provides a silver ferrite / indium tin sulfide composite Z-type photocatalyst. The silver ferrite / indium tin sulfide composite Z-type photocatalyst uses indium tin sulfide as a carrier, and the indium tin sulfide is coated with silver ferrite.

[0006] The silver ferrite / indium tin sulfide composite Z-type photocatalyst is further improved, and the mass percentage of silver ferrite to indium tin sulfide is 1-10wt%. The preparation method of the silver ferrite / indium tin sulfide composite Z-type photocatalyst comprises the following steps:

[0007] (1) adding an iron-containing compound and a silver-containing compound to a dispersant and stirring to form a mixed solution A, and dropping an alkaline solution to form a mixed solution B, and subjecting the mixed solution B to a hydrothermal reaction; after the reaction is completed and cooled to room temperature, washing is performed to remove excess ions and drying is performed to obtain silver ferrite;

[0008] (2) A certain amount of silver ferrite, tin salt, indium salt and sulfur source are added to a dispersant, ultrasonically dispersed and stirred to form a mixed solution C, and the mixed solution C is transferred to a hydrothermal reactor for hydrothermal reaction. After cooling to room temperature, the mixed solution is washed and dried to obtain a silver ferrite / indium tin sulfide composite Z-type photocatalyst.

[0009] In step (1), the iron-containing compound is ferric nitrate nonahydrate, the silver-containing compound is silver nitrate, the dispersant is deionized water, and the molar ratio of ferric nitrate nonahydrate to silver nitrate is 1:1. The stirring condition is at room temperature and the stirring time is 15 minutes. The alkaline solution is 2 mol / L sodium hydroxide or potassium hydroxide solution, and the amount added is 7 mL. The hydrothermal reaction conditions are 150-200°C; the time is 12-36 hours.

[0010] In step (2), the tin salt is crystalline tin tetrachloride, the indium salt is indium trichloride tetrahydrate; the sulfur source is thioacetamide. The molar ratio of the tin salt to the indium salt is 1 to 4, and the molar ratio of the tin salt to the sulfur source is 1:9 to 12; the power of the ultrasound is 70 to 100 W; the ultrasound time is 5 min to 10 min. The hydrothermal reaction temperature is 110°C to 130°C, and the time is 4h to 8h.

[0011] The second aspect of the present invention provides the application of silver ferrite / indium tin sulfide composite Z-type photocatalyst in the degradation of antibiotic wastewater, specifically mixing the silver ferrite / indium tin sulfide composite Z-type photocatalyst with an aqueous solution containing antibiotics, performing dark adsorption in the dark, and waiting for adsorption equilibrium. A photocatalytic reaction is carried out under light conditions to complete the degradation of tetracycline hydrochloride. Further, the dosage of the silver ferrite / indium tin sulfide composite Z-type photocatalyst is 0.2 g / L, the aqueous solution containing antibiotics is an aqueous solution containing tetracycline hydrochloride, and the concentration of tetracycline hydrochloride is 20 mg / L. The dark adsorption time is 1h, the illumination condition is a 300 W xenon lamp, and the photocatalytic reaction time is 120min.

[0012] Compared with the prior art, the technical solution provided by the present invention has the following advantages:

[0013] (1) The present invention provides a preparation method and application of a silver ferrite / indium tin sulfide composite Z-type photocatalyst, which increases its photocatalytic stability, improves carrier lifetime, reduces electron-hole recombination rate, and can efficiently degrade antibiotic wastewater.

[0014] (2) The present invention provides a method for preparing a silver ferrite / indium tin sulfide composite Z-type photocatalyst, which has the advantages of easy control of conditions, no by-products generated during the preparation process, low secondary pollution, and little pollution to the environment.

[0015] (3) The silver ferrite / indium tin sulfide composite Z-type photocatalyst of the present invention can be used for the efficient degradation of antibiotics in water, and has the advantages of stable photocatalytic performance and high efficiency in pollutant degradation, providing theoretical guidance for the optimized preparation and application of indium sulfide compound composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Scanning electron microscope images of photocatalysts, where (a) is silver ferrite, (b) is indium tin sulfide, and (c) is 6wt% silver ferrite / indium tin sulfide composite material. Figure 2 XRD diagrams of the silver ferrite / indium tin sulfide composite Z-type photocatalyst prepared in Examples 1 to 5, the silver ferrite prepared in Comparative Example 1, and the indium tin sulfide prepared in Comparative Example 2. Figure 3 The photocatalytic performance diagrams of the silver ferrite / indium tin sulfide composite Z-type photocatalyst in Examples 1 to 5 and pure silver ferrite and indium tin sulfide. DETAILED DESCRIPTION

[0017] The present invention is described in detail below in conjunction with specific embodiments. The materials and instruments used in the following examples are all commercially available.

[0018] Embodiment 1:

[0019] A method for preparing a silver ferrite / indium tin sulfide composite Z-type photocatalyst, using indium tin sulfide as a carrier, and silver ferrite is coated on the indium tin sulfide. Specifically, the method comprises the following steps:

[0020] (1) Weigh 2 mmol of ferric nitrate nonahydrate and 2 mmol of silver nitrate and dissolve them in 45 mL of ultrapure water. Slowly add 7 mL of 2 mol / L NaOH solution into the solution and stir for 15 min. Pour the solution into a hydrothermal reactor for hydrothermal reaction at 170 °C for 24 h. After cooling to room temperature, wash the precipitate with deionized water and ethanol respectively. Finally, dry the product at 70 °C for 24 h to obtain silver ferrite.

[0021] (2) Crystalline tin tetrachloride and indium trichloride were dissolved in 20 wt% acetic acid aqueous solution to prepare 0.6 mmol / L (Sn 4+ ) and 2.4 mmol / L (In 3+ ) aqueous solution. Weigh 0.0097 g of silver ferrite and dissolve it in a flask containing 60 mL of deionized water, and ultrasonicate for 30 minutes. Add 1 mL of Sn 4+ and 1 mL In 3+Aqueous solution and excess thioacetamide (TAA, 10 mmol) were added, and the solution was then placed in a hydrothermal reactor for reaction at 120°C for 6 hours. After the reaction was completed, the hydrothermal reactor was naturally cooled to room temperature. The product was collected by centrifugation, then washed several times with deionized water and anhydrous ethanol, and finally dried at 70°C for 24 h. The silver ferrite / indium tin sulfide composite Z-type photocatalyst was obtained, named 2wt% AFO / SIS.

[0022] Comparative Example 1:

[0023] A method for preparing silver ferrite,

[0024] Weigh 2 mmol of ferric nitrate nonahydrate and 2 mmol of silver nitrate and dissolve them in 45 mL of ultrapure water. Slowly add 7 mL of 2 mol / L NaOH solution into the solution and stir for 15 min. Pour the solution into a hydrothermal reactor for hydrothermal reaction at 170 °C for 24 h. After cooling to room temperature, wash the precipitate with deionized water and ethanol respectively. Finally, dry the product at 70 °C for 24 h to obtain silver ferrite.

[0025] Comparative Example 2:

[0026] Crystalline tin tetrachloride and indium trichloride were dissolved in 20 wt% acetic acid aqueous solution to prepare 0.6 mmol / L (Sn 4+ ) and 2.4 mmol / L (In 3+ ) aqueous solution. In a beaker containing 60 mL of deionized water, add 1 mL of Sn 4+ and 1 mL In 3+ Aqueous solution, and excess thioacetamide (TAA, 10 mmol). The solution was then placed in a hydrothermal reactor and reacted at 120°C for 6 hours. After the reaction was completed, the hydrothermal reactor was naturally cooled to room temperature. The product was collected by centrifugation, then washed several times with deionized water and anhydrous ethanol, and finally dried at 70°C for 24 h. Pure indium tin sulfide photocatalyst was obtained.

[0027] Embodiment 2:

[0028] The difference between this embodiment and embodiment 1 is that the content of silver ferrite in the indium tin sulfide precursor is 0.0194 g, and the rest is the same as embodiment 1.

[0029] The silver ferrite / indium tin sulfide composite Z-type photocatalyst prepared in Example 2 is named 4wt% AFO / SIS. Example 3:

[0030] The difference between this embodiment and embodiment 1 is that the content of silver ferrite in the indium tin sulfide precursor is 0.0291 g, and the rest is the same as embodiment 1. The silver ferrite / indium tin sulfide composite Z-type photocatalyst prepared in embodiment 3 is named 6wt% AFO / SIS.

[0031] Embodiment 4:

[0032] The difference between this embodiment and embodiment 1 is that the content of silver ferrite in the indium tin sulfide precursor is 0.0388 g, and the rest is the same as embodiment 1. The silver ferrite / indium tin sulfide composite Z-type photocatalyst prepared in embodiment 4 is named 8wt% AFO / SIS.

[0033] Embodiment 5:

[0034] The difference between this embodiment and embodiment 1 is that the content of silver ferrite in the indium tin sulfide precursor is 0.0485 g, and the rest is the same as embodiment 1. The silver ferrite / indium tin sulfide composite Z-type photocatalyst prepared in embodiment 5 is named 10wt% AFO / SIS.

[0035] Embodiment 6:

[0036] A silver ferrite / indium tin sulfide composite Z-type photocatalyst is used to degrade wastewater containing antibiotics, specifically using the silver ferrite / indium tin sulfide composite Z-type photocatalyst to degrade wastewater containing tetracycline, comprising the following steps:

[0037] Weigh 0.01 g of the silver ferrite / indium tin sulfide composite Z-type photocatalysts (2wt% AFO / SIS, 4wt% AFO / SIS, 6wt% AFO / SIS, 8wt% AFO / SIS and 10wt% AFO / SIS) prepared in Examples 1-5, the silver ferrite prepared in Comparative Example 1, and the indium tin sulfide prepared in Comparative Example 2, respectively, and add them to 50 mL of tetracycline wastewater with a concentration of 20 mg / L, and stir magnetically for one hour under light-proof conditions to reach adsorption equilibrium. Turn on the light source and irradiate under visible light (λ≥420 nm) for photocatalytic reaction for 120 min to complete the treatment (degradation) of the antibiotic wastewater.

[0038] Determination of degradation efficiency: 3 mL of the photocatalytic degradation solution in the reaction container was aspirated every 15 minutes, filtered with a 0.22 μm filter head, and the filtrate was detected on a UV-visible spectrophotometer.

[0039] from Figure 3 It can be seen that:

[0040] The degradation efficiency of the silver ferrite / indium tin sulfide composite Z-type photocatalyst (2wt% AFO / SIS) prepared in Example 1 of the present invention for tetracycline was 83.25% after 120 minutes of photocatalytic reaction.

[0041] The degradation efficiency of the silver ferrite / indium tin sulfide composite Z-type photocatalyst (4wt% AFO / SIS) prepared in Example 2 of the present invention for tetracycline was 86.96% after 120 minutes of photocatalytic reaction.

[0042] The degradation efficiency of the silver ferrite / indium tin sulfide composite Z-type photocatalyst (6wt% AFO / SIS) prepared in Example 3 of the present invention for tetracycline was 90.91% after 120 minutes of photocatalytic reaction.

[0043] The degradation efficiency of the silver ferrite / indium tin sulfide composite Z-type photocatalyst (8wt% AFO / SIS) prepared in Example 4 of the present invention for tetracycline was 85.79% after 120 minutes of photocatalytic reaction.

[0044] The degradation efficiency of the silver ferrite / indium tin sulfide composite Z-type photocatalyst (10wt% AFO / SIS) prepared in Example 5 of the present invention for tetracycline was 76.14% after 120 minutes of photocatalytic reaction.

[0045] The degradation efficiency of the silver ferrite prepared in Comparative Example 1 of the present invention on tetracycline is 30.55% after the photocatalytic reaction for 120 minutes.

[0046] The degradation efficiency of indium tin sulfide prepared in comparative example 2 of the present invention on tetracycline after 120 minutes of photocatalytic reaction is 74.46%.

[0047] The above results show that the silver ferrite / indium tin sulfide composite Z-type photocatalyst of the present invention can effectively remove tetracycline from wastewater, and the silver ferrite / indium tin sulfide composite Z-type photocatalyst in Example 3 has the best removal effect on tetracycline, with a degradation efficiency of 90.91%, which is 2.97 and 1.22 times higher than that of pure silver ferrite and indium tin sulfide, respectively. This indicates that silver ferrite and indium tin sulfide form a heterojunction structure, which improves the photocatalytic activity.

[0048] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a silver ferrite / indium tin sulfide composite Z-type photocatalyst, characterized in that: The following steps are involved: (1) adding an iron-containing compound and a silver-containing compound to a dispersant and stirring to form a mixed solution A, and dropping an alkaline solution to form a mixed solution B, and subjecting the mixed solution B to a hydrothermal reaction; after the reaction is completed and cooled to room temperature, washing is performed to remove excess ions and drying is performed to obtain silver ferrite; (2) A certain amount of silver ferrite, tin salt, indium salt and sulfur source are added to a dispersant, ultrasonically dispersed and stirred to form a mixed solution C, and the mixed solution C is transferred to a reactor for hydrothermal reaction. After cooling to room temperature, the mixed solution is washed and dried to obtain a silver ferrite / indium tin sulfide composite Z-type photocatalyst.

2. The preparation method according to claim 1, characterized in that: In the step (1), the iron-containing compound is ferric nitrate nonahydrate, the silver-containing compound is silver nitrate, the molar ratio of ferric nitrate nonahydrate to silver nitrate is 1:1, the dispersant is deionized water, and the stirring speed is 400-600 rpm.

3. The preparation method according to claim 1, characterized in that: In the step (1), the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution; the concentration is 2 mol / L, and the amount added is 7 mL.

4. The preparation method according to claim 1, characterized in that: In the step (1), the hydrothermal reaction temperature is 150-200°C and the reaction time is 12-36 hours.

5. The preparation method according to claim 1, characterized in that: In the silver ferrite / indium tin sulfide composite Z-type photocatalyst, the mass percentage of silver ferrite to indium tin sulfide is 1~10 wt%.

6. The preparation method according to claim 1, characterized in that: In the step (2), the molar ratio of the tin salt, the indium salt and the sulfur source is 1:4:9-12.

7. The preparation method according to claim 1, characterized in that: In the step (2), the ultrasonic power is 70-100 W; and the ultrasonic time is 5 min to 10 min.

8. The preparation method according to claim 1, characterized in that: In the step (2), the hydrothermal reaction temperature is 110° C. to 130° C. and the reaction time is 4 h to 8 h.

9. Use of the silver ferrite / indium tin sulfide composite Z-type photocatalyst prepared by the preparation method according to any one of claims 1 to 8 in sewage treatment, characterized in that: The silver ferrite / indium tin sulfide composite Z-type photocatalyst is directly added to the antibiotic wastewater, first reaching adsorption equilibrium in the dark, and then undergoing photocatalytic reaction under light conditions to complete the degradation of the antibiotic wastewater.

10. The use according to claim 9, characterized in that: The dosage of the silver ferrite / indium tin sulfide composite Z-type photocatalyst is 0.2 g / L, the antibiotic wastewater is tetracycline wastewater, the tetracycline concentration is 20 mg / L, the lighting condition is a 300 W xenon lamp, and the photocatalytic reaction time is 120 min.

Citation Information

Patent Citations

  • Method for preparing SnIn4S photocatalyst through low-temperature coprecipitation method

    CN103657686A

  • Preparation method and application of molybdenum carbide / zinc indium sulfide composite photocatalyst

    CN108043436A

Cited By

  • Method for preparing an aerogel material and use thereof

    CN118698561B